Daur Ulang Sampah Aluminium Foil Kemasan Aseptik Menjadi Tawas - Lilis Anggreani; Elvi Yenie; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Aseptic packaging is one of the largest contributors of garbage where the production reaches 4 billion pieces per year. The handling of this garbage haven’t maximum yet, so it can be an opportunity to recycle the aluminum foil into alum. The aluminum foil on aseptic packaging contents 52% of aluminum, measured with Atomic Absorption Spectrophotometry (AAS). The product to make alum are 20%, 30% and 40% of KOH and the variation of 6M, 8M, and 10M H2SO4. The research show that the maximum produced of alum was mostly produced by using 40% of KOH and 6M of H2SO4 which produced 19,91 gr of alum from 3 gr of raw materials or equal to 72.69%. The characteristic of the potassium alum has content 4.59% of aluminum and 0% of insoluble substances.Keywords: Aluminum, Aseptic packaging, Potassium alum